MENGHIDUPKAN DAKWAH PROFETIK DI ERA MILLENIAL - Alfiana Yuniar Rahmawati (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2020)
Da’wah activities become the obligation of all mankind after the death of the Prophet Muhammad SAW. Contemporary da’wah should be able to replace the classic da’wah because of the sophistication of technology that provides convenience in the process of spreading Islamic da’wah. But unfortunately, this convenience triggers a decline in the quality of propaganda. Some of the da’wah content that is more prioritizing the utterance of hatred, public lies (hoaxes), to the spread of the issue of radicalism and terrorism. For this reason, the presence of millennial generation that is synonymous with technology has become a major asset in carrying out missionary mission. In the ethics of da’wah, millennials must begin to be directed to prophetic preaching or preaching in the style of Rosulullah SAW, namely to call for goodness (amar ma’ruf), prevent munkar (nahi munkar), and believe fully in Allah SWT as the all powerful Essence. It aims to restore the essence of the teachings of islam as taught in the time of the Prophet Muhammad SAW. Aktivitas dakwah menjadi kewajiban seluruh umat manusia setelah wafatnya Nabi Muhammad SAW.Dakwah kontemporer seharusnya bisa menggantikan dakwah klasik karena adanya kecanggihan teknologi yang memberikan kemudahan dalam proses penyebaran dakwah Islam. Namun sayangnya, kemudahan ini memicu menurunnya kualitas dakwah.Beberapa konten dakwah yang ada lebih mengedepankan ujaran kebencian, kebohongan publik (hoax), sampai pada penyebaran isu radikalisme dan terorisme.Untuk itu, hadirnya generasi milenial yang identik dengan teknologi, menjadi aset utama dalam menjalankan misi dakwah.Dalam etika berdakwah,para milenialharus mulai diarahkan pada dakwah profetik atau dakwah ala Rasulullah SAW, yaitu menyeru kepada kebaikan (amar ma’ruf), mencegah kemungkaran (nahi munkar), serta percaya sepenuhnya kepada Allah SWT sebagai Dzat yang maha segala-galanya. Hal ini bertujuan untuk mengembalikan esensi dari ajaran agama islam seperti yang diajarkan pada masa Rasulullah SAW.